Genetic Variability and Association Studies on Grain Yield Components in F2 Populations of Black Rice (Oryza sativa L.) of Manipur - S., Bhuvaneswari; Kumar, Sudhir; I, Meghachandra Singh; Takhellambam, Sunanda; S., Shashidhar K.; Y, Rajen Singh; N, Prakash (Indian Journal of Hill Farming, 2016)
The F2 segregating populations of two black rice crosses viz., cross I ( Chakhao amubi Ã—RCM 23 ) and cross II (RCM 14Ã—RCM 23) were evaluated during Kharif 2014 for assessment of genetic variability, association and path analysis of yield and yield components under transplanted rainfed lowland condition. In both populations, all traits except panicle length and days to first flowering showed moderate to high Phenotypic Coefficient of Variation (PCV) and Genotypic Coefficient of Variation (GCV). Heritability were moderate to high for all the traits coupled with high genetic advance as percent mean except for panicle length and days to first flowering. The correlation studies revealed that in both crosses, productive tillers per plant, filled spikelets, spikelet fertility and 1000 grains weight showed significant positive correlation with grain yield whereas days to first flowering showed significant negative correlation with grain yield in cross I whereas it was negative non-significant in Cross II. Path analysis revealed that productive tillers per plant and filled spikelets per panicle had high positive direct effect on grain yield.